Prevalence of obesity and overweight and associated factors among financial institution workers in Accra Metropolis, Ghana: a cross sectional study. (December 2015) - Addo, Prince; Nyarko, Kofi; Sackey, Samuel; Akweongo, Patricia; Sarfo, Bismark
Abstract Background Certain professions are associated with low physical activity. Workers in such professions spend the most part of their adult working lives less engaged in physical activity if they don't consciously exercise outside of working hours. This increases their risk of obesity and its associated diseases. This study determined the prevalence of obesity and overweight and associated factors among workers of a financial institution in Accra Metropolis, Ghana. Methods A cross-sectional study was conducted among 180 workers of a financial institution in Accra using the World Health Organization's STEPS (STEPwise approach) instrument for non-communicable disease risk factor surveillance. Relevant sociodemographic information were recorded and BMI was computed for each respondent. Results The overall prevalence of obesity and overweight among the bank workers was 55.6 % (17.8 % obese and 37.8 % overweight). After adjusting for other variables, physical activity (OR = 0.34, 95 % CI = 0.13–0.89, p = 0.03), alcohol consumption (OR = 3.00, 95 % CI = 1.35, 6.68, p = 0.007), marital status (OR = 2.74, 95 % CI = 0.96–7.85, p = 0.04), sex (OR = 2.78, 95 % CI = 1.23–6.33, p = 0.01), and age (OR = 1.10, 95 % CI = 1.01–1.20, p = 0.036) were significantly associated with obesity and overweight. Conclusion Being physically inactive, consumption of alcohol, being married and a female, in addition to old age, increase the risk of obesity and overweight significantly. These factors should inform policy makers in developing strategies to reduce the burden of obesity and overweight among this category of workers.